(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تناولت هذه الدراسة تحديد تراكيزالمركبات الهيدروكربونية الأليفاتية (AHs) في المياه والرسوبيات البحرية لشاطئ مدينـة بانياس، التي تعد إحدى النقاط الساخنـة على شاطئ البحـر الأبيض المتوسط Hot Spots، حيث تم اختيار ستة مواقـع ابتداءً من عرب الملك شمالاً، حتى الفنار جنوباً ، خلال الفترة الممتدة من أيار2000 إلى حزيران 2001 . أجريت الدراسة التحليلية لمركبات الـ (AHs) بالاعتماد على تقانة الكروماتوغرافيا الغازية (GC) وباستخدام كاشف تشرد اللهب (FID)، وأظهرت النتائج وجود تراكم للمركبات الهيدروكربونية الأليفاتية في رسوبيـات هذه المنطقة، وتراوحت التراكيز الكليـة لمركبات الـ (AHs) مابين 4.23µg/g في محطـة عرب الملك و21.12µg/g في المحطـة المقابـلة لمصب مجرور مصفاة بانياس . من ناحية أخرى حاولنا إعطاء صورة أوليـة عن المصادر المحتمـلة للمركبـات الهيدروكربونية الأليفاتيـة في شاطئ مدينـة بانياس بالاعتماد على بعض القرائن والأدلة التي توضح ذلك مثل Pristane/Phytane و∑n-alkane /n-C16 وOdd/Even(CPI) . This study deals with the determination of the concentration of (AHs) in water and marine sediments of Banias city coast which is considerd one of the Hot Spots on the Medd.sea coast, six sampling points were selected as from (Arab almalek) in the north, till (Alfanar) in the south, during the period between May 2000 till June 2001. The analytical study was performed on (AHs) compounds employing the Gas Chromatography technique (GC), using flame ionization detector (FID), results revealed accumulation of the (AHs) compounds in the sediments of this region, and the total concentrations for (AHs) compounds ranged between 4.23µg/g in (Arab almalek) station and 21.12µg/g in the station opposite to the discharge point of Banias refinery sewage line. On the other hand, we attempted to disclose primary image for the potential sources of the (AHs) compounds at Banias city coast relying on some indices and proves that explain this like: Σn-alkane/n-C16 & Pristane/Phytane & Odd/Even (CPI).